Accounting treatment recommendations for bottom-up shareholding increase - Lixia Wang; Vigdis W. Boasson; Guoqing Xu (Cogent Business & Management, 2024)
An increasing number of companies in China are adopting bottom-up shareholding increases to incentivize employees and stabilize stock prices. However, a research gap exists regarding China's current accounting regulations for handling bottom-up equity incentives. This study aims to address this research gap by clarifying the accounting treatment of bottom-up shareholding increases by publicly traded companies in China. Specifically, it seeks to analyze the economic essence of such transactions and propose a framework for their accounting treatment. To achieve the objectives, this study conducts a comprehensive analysis of the relevant provisions of current corporate accounting standards in China. Additionally, it considers perspectives from contract law to provide a holistic understanding of the issue. Based on the analytical results, this study proposes that the economic essence of a publicly traded company's implementation of a bottom-up shareholding increase is akin to the sponsor's equity donation to the company. Consequently, it suggests that such transactions can be accounted for similarly to capital donations by controlling shareholders to publicly traded companies. Hence, this research offers valuable reference and guidance for the accounting treatment of bottom-up shareholding increases by publicly traded companies in China. Furthermore, it holds significant importance in the context of further standardizing China's corporate accounting practices and contributes to international accounting standards.
Keywords: 650; Bottom-up shareholding increase; employee incentives; accounting regulations; accounting treatment